Eugenol derivatives with potential insecticide activity - Coelho, José Ricardo Alves (2021)
In the present work, semisynthetic eugenol derivatives were obtained through epoxidation reaction followed by epoxide opening with nucleophiles, such as sodium azide and sodium cyanide. The optimization of the various reactions was performed using different experimental conditions. The main objective behind obtaining these eugenol derivatives was their evaluation as alternative insecticides, thus the biological activity of all compounds was compared to a commercial synthetic insecticide and tested against Sf9 (Spodoptera frugiperda) insect cell line.